Co‐infection of Nucleospora cyclopteri (Microsporidia) and Kudoa islandica (Myxozoa) in farmed lumpfish, Cyclopterus lumpus L., in Norway: a case report. Issue 4 (10th April 2015) - Alarcón, M; Thoen, E; Poppe, T T; Bornø, G; Mohammad, S N; Hansen, H
Abstract: This study describes a co‐infection of Kudoa islandica (Myxozoa) and Nucleospora cyclopteri (Microsporida) in farmed lumpfish, Cyclopterus lumpus L., in Norway. Several other parasites ( Cryptocotyle sp., protozoan ciliates and Gyrodactylus sp.) were also found in gills. In June 2013, the mortality in a farmed lumpfish population increased to 65%. Lumpfish showed erratic swimming behaviour and loss of weight. At necropsy, nodules in the kidney were the only visible lesions. Histologically, all fish showed severe changes with gill inflammation and necrosis in the spleen, kidney and liver. Haemorrhages and necrosis were observed in some hearts. Intracellular microsporidians associated with the lesions were detected in most organs using histological examination and Calcofluor White. Kudoa spores were diagnosed in the skeletal muscle, but no inflammatory response was associated with the presence of the plasmodia. Comparison of 18S ribosomal DNA sequences showed 100% similarity to Kudoa islandica and Nucleospora cyclopteri. Kudoa islandica and N. cyclopteri have previously been described associated with lesions in wild lumpfish in Iceland. In the present case, N. cyclopteri is believed to be the main cause of systemic pathology. This is the first description of K. islandica and N. cyclopteri causing pathology in farmed lumpfish in Norway.